The Impact of External Factors on Accounting Information System (AIS) Usage - Ainon Ramli (2013)
The study focused on external factors of training, experience and internal expertise of the use of Accounting Information Systems (AIS) in three, four, and five star rated hotels. The data from the survey were collected through a postal questionnaire to senior accounting managers in three, four, and five star rated hotels. The data were analyzed using Partial Least Squares (PLS), which is the PLS-Graph Beta version 3.0. It was found that experience and internal expertise influenced the usage of the AIS, however, training was not significant to AIS users in the hotel industry in Malaysia. Using an extension of Technology Acceptance Model (TAM), this study reveals the wide use of computerized accounting systems.